2011
DOI: 10.1007/s00044-011-9688-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, evaluation of 6,8-dibromo-2-aryl-2,3-dihydroquinolin-4(1H)-ones in MCF-7 (breast cancer) cell lines and their docking studies

Abstract: A series of novel 6,8-dibromo-2-aryl-2,3-dihydroquinolin-4(1H)-ones have been synthesized and evaluated in vitro (in MCF-7 breast cancer cell lines). Compounds 5a, 5d, 5e, and 5g exhibited potent GI 50 and TGI values compared with reference standard and compounds 5b and 5c showed moderate activity. The docking studies (in silico) were conducted to recognize the hypothetical binding motif of the title compounds within the active site of aromatase enzyme employing GOLD docking software. The binding mode and SAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…amounts through dietary sources and food supplements (more recently termed 'nutraceuticals'). It has been demonstrated that several flavanoid derivatives are potent AIs as well as effective antiproliferative agents against MCF-7 (breast cancer) cell lines (12,13). This substantiates our hypothesis that the flavonoid scaffold could churn out to be a milestone in developing the next generation of safer AIs.…”
supporting
confidence: 85%
“…amounts through dietary sources and food supplements (more recently termed 'nutraceuticals'). It has been demonstrated that several flavanoid derivatives are potent AIs as well as effective antiproliferative agents against MCF-7 (breast cancer) cell lines (12,13). This substantiates our hypothesis that the flavonoid scaffold could churn out to be a milestone in developing the next generation of safer AIs.…”
supporting
confidence: 85%
“…Although 2-aminobenzamide is commercially available and has been used in several transformations before, to our knowledge, direct bromination of this compound has not been explored so far. On the other hand, the analogous 2'-aminoacetophenone has been found to undergo bromination with NaBr-oxone in acetonitrile [18], Br 2 in acetic acid [19], or N-bromosuccinimide (NBS) in CHCl 3 -CCl 4 mixture [20] to afford 2-amino-3,5-dibromoacetophenone in high yield. Based on these literature precedents, we subjected anthranilamide 1 to NBS (2.5 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…The most active compounds (Fig. 14) form a hydrogen bonding with Ser 478 or Asp 309 amino acids of the active site, which probably account, according the authors, for their better activity compared to other analogs of the series [88]. Fig.…”
Section: Another Docking Model Was Determined For the Interaction Betmentioning
confidence: 92%
“…The same research group of the prior cited work also determined a docking model for 6,8-dibromo-2-aryl-2,3dihydroquinolin-4(1H)-ones, which were evaluated in vitro (for MCF-7 breast cancer cell lines) [88]. The docking stud-ies were determined to recognize the binding motif of the title compounds within the active of aromatase enzyme employing GOLD docking software using the same X-ray crystal structure of human placental microsomal aromatase (PDB ID: 3EQM) [78].…”
Section: Another Docking Model Was Determined For the Interaction Betmentioning
confidence: 99%